1995
DOI: 10.1002/cne.903630105
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the morphology and function of gastric‐ and intestine‐sensitive neurons in the nucleus of the solitary tract

Abstract: This study employed single cell recording and intracellular iontophoretic injection techniques to characterize and label gastric- and/or intestine-sensitive neurons in the rat nucleus of the solitary tract (NST). It was possible to divide our sample of NST neurons into three broad groups based on their response to increased intra-gastric and intra-duodenal pressure. Group 1 cells (N = 14) were excited by duodenal distention but were not responsive to gastric stimulation. Most of these intestine-sensitive neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…The NTS comprises a vast array of neurons with different neurochemical and morphological properties (Zhang et al, 1995;Blessing, 1997;Deuchars et al, 2000;Paton et al, 2000;Travagli et al, 2006). Recently, Bailey et al (2006a) correlated morphological and electrophysiological properties of NTS neurons with their projections to either the hypothalamus or the CVLM area.…”
Section: Implications For the Control Of Food Intakementioning
confidence: 99%
“…The NTS comprises a vast array of neurons with different neurochemical and morphological properties (Zhang et al, 1995;Blessing, 1997;Deuchars et al, 2000;Paton et al, 2000;Travagli et al, 2006). Recently, Bailey et al (2006a) correlated morphological and electrophysiological properties of NTS neurons with their projections to either the hypothalamus or the CVLM area.…”
Section: Implications For the Control Of Food Intakementioning
confidence: 99%
“…but also in their somata size or shape (Zhang et al 1995;Fogel et al 1996;Jarvinen & Powley, 1999). Fogel et al (1996) have recently provided strong evidence for the existence of a relationship between structure and function in the DMV.…”
mentioning
confidence: 99%
“…In particular, Smith's group reported that NTS neurons receiving sensory information from the corpus can be classified into three subgroups [14]. The vast heterogeneity of morphological features of gastrointestinal NTS neurons was reinforced further by studies of Fogel's group, which classified NTS neurons into three subpopulations based upon their different responses to gastrointestinal stimulations [34].…”
Section: Discussionmentioning
confidence: 99%
“…Some membrane properties of cNTS neurons, however, seem to indicate that these neurons have characteristics that distinguish them from other NTS neurons, most noticeably the smaller soma area and the higher input resistance [12,14,17,19,26,32,34]. These electrophysiological membrane features would seem to be best suited to signaling the fast dynamic changes in esophageal pressure observed during the passage of a bolus in the esophagus, since even minute changes in neurotransmitter release would induce large changes in the membrane potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation